2019
DOI: 10.9734/ejnfs/2019/v9i430081
|View full text |Cite
|
Sign up to set email alerts
|

Physico-chemical Characterization of Palm Kernel Oil Extracted from the Seeds of Two Varieties of Oil Palm (Elaeis guineensis Jacq.) for Possible Use in Feed or Food

Abstract: This study was carried out in order to assess the quality of the type of palm kernel oil suitable for the alternative in animal oil in feed or food. To reach this objective, oil D and oil T extracted respectively from the seeds of the varieties Dura and Tenera of oil palm (Elaeis guineensis Jacq.) by the Soxhlet method using hexane as a solvent were analyzed for their physicochemical characteristics. The results obtained show that the values for the physical parameters (Oil yield, density and percentage of imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
7
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 21 publications
4
7
1
Order By: Relevance
“…The extraction of the fat content showed that the palm kernel oil yields obtained for these two varieties were around 50% (Table 2). This value fell in that obtained by Yapi and Kouadio (2019) and also in that indicated by the Codex Alimentarius (2015). It is also noted that the oil yields obtained were similar to that obtained by Pickard (2005), but fell below the range of 75-80% found by Asuquon (2008).…”
Section: The Fat Contentsupporting
confidence: 67%
See 2 more Smart Citations
“…The extraction of the fat content showed that the palm kernel oil yields obtained for these two varieties were around 50% (Table 2). This value fell in that obtained by Yapi and Kouadio (2019) and also in that indicated by the Codex Alimentarius (2015). It is also noted that the oil yields obtained were similar to that obtained by Pickard (2005), but fell below the range of 75-80% found by Asuquon (2008).…”
Section: The Fat Contentsupporting
confidence: 67%
“…Oil extraction was carried out by using the Soxhlet (250 mL -Allihn -LENZ) method with hexane as a solvent which gives the best oil yield with solid sample according to Mohd-Setapar et al (2004). For the process of extraction, the method used was that described by Yapi and Kouadio (2019). At the end of this extraction process, the oil was recovered by evaporating off the solvent using rotary evaporator where it was heated at 70 °C until the solvent finally evaporated and leaving behind the extracted oil.…”
Section: Oil Extractionmentioning
confidence: 99%
See 1 more Smart Citation
“…Oil extraction was carried out by using the Soxhlet method described by Yapi and Kouadio (2019). The solvent used was hexane which gives the best oil yield with solid sample according to Mohd-Setapar et al (2004).…”
Section: Oil Extractionmentioning
confidence: 99%
“…In Côte d'Ivoire and many African countries, oil extracted from the kernel is used for seasoning the dishes and as food preservative (Yapi & Kouadio, 2019). Previously, Agboola et al, (2015) have shown that palm kernel oil contained saturated fatty acids as well as monounsaturated and polyunsaturated fatty acids used in African dishes.…”
Section: Introductionmentioning
confidence: 99%